Eclectic Approach to English Textbook for Eleventh Grade Students of Senior High School - Widhiya Ninsiana; Ader Laepe; Maram Taher Ali; Ahmadullah Al-Adibi Ash-Sholihi (Ta'dib, 2022)
The objective of this study is to determine the effects and advantages of using an eclectic approach in English textbooks for the eleventh grade of Indonesian senior high school students. The study was designed using qualitative research methods, with the objective of generating descriptive data in the form of words, phrases, and sentences. The study found the effect of using an eclectic approach in an English textbook for the eleventh-grade students of the Islamic High School (MAN) 1 of Metro. The use of an eclectic approach enabled teachers to use conversation, forming study group, loud-speaker, game, and body movement at the appropriate moment and arrangement while delivering the material. Among the advantages of using this method is that it allows the teacher to make the material more interesting, vary the teaching, increase confidence in delivering material, and liven up the bilingual situation. In addition, eclectic approach allows students to understand the English material more easily and relax while learning English. The study found that the use of an eclectic approach in English textbooks for the eleventh-grade students in an Islamic senior high school (MAN) 1 of Metro has a significant impact on both teachers and students when it comes to teaching and learning English.